The Religious Manager - Senger, John (Academy of Management Journal, 1970)
Managers' choice of goals, their rating of subordinates, and various organizational and biographical data were related to the managers' Religion Value score as measured by judging religious terms against semantic differential scales. Broadly, the more religious managers were found to be more socially and humanistically oriented and relatively disinterested in personal earnings and company profits. They appeared to be less ?self-actualizing.? The managers with high Religion Value scores tended to be most frequently in marketing, to have studied business administration, to be generally less well educated, to tend to come from lower classes, to participate in community and professional activities, to engage in active rather than sedentary hobbies, to be higher rated in all-around competence, but not to hold the top position in the company.